Clinical Presentation of Complete Hydatidiform Mole and Partial Hydatidiform Mole at a Regional Trophoblastic Disease Center in the United States Over the Past 2 Decades. Issue 2 (1st February 2016) - Sun, Sue Yazaki; Melamed, Alexander; Joseph, Naima T.; Gockley, Allison Ann; Goldstein, Donald Peter; Bernstein, Marilyn R.; Horowitz, Neil S.; Berkowitz, Ross Stuart
Abstract : Objective: The aim of this study was to compare the clinical presentation and incidence of postmolar gestational trophoblastic neoplasia (GTN) among cases of complete mole (CM) and partial mole (PM) from 1994 to 2013. Methods: This study included all cases of patients with CM and PM from our trophoblastic disease center between 1994 and 2013. Their clinical and pathologic reports were reviewed. Gestational age at evacuation, features of clinical presentation, human chorionic gonadotropin levels, and the rate of progression to GTN were compared. Results: The median gestational age at evacuation was 9 weeks for CM and 12 weeks for PM ( P < 0.001). Patients with PM had lower pre-evacuation serum human chorionic gonadotropin levels ( P < 0.001), and they were also less likely to present with vaginal bleeding ( P < 0.001), biochemical hyperthyroidism ( P < 0.001), anemia ( P < 0.001), uterine size greater than dates ( P < 0.001), and hyperemesis ( P = 0.002). Consequently, patients with PM were less likely to have been clinically diagnosed as moles compared with CM prior to uterine evacuation ( P < 0.001). The development of GTN occurred in 17.7% (33/186) and 4.1% (7/169) of patients with CM and PM, respectively ( P < 0.001). Conclusions: This study indicates that, at our center over the past 20 years, both CM and PM were usually evacuated in the first trimester of pregnancy. Because CM more commonly presents with the signs and symptoms of molar disease than PM, CM is more commonly diagnosed prior to evacuation.